SEMANTIC PROSODY AND PREFERENCE OF “HEALTHY” AND “UNHEALTHY” COLLOCATIONS IN COVID-19 CORPUS - Nafilaturif'ah Nafilaturif'ah; Mohamad Irham Poluwa (Universitas Islam Sumatera Utara (UISU), 2021)
This study is conducted in order to know the collocations of ‘healthy’ and ‘unhealthy’ as well as to explore the lexical meaning of those collocations. Corpus-based approach is employed in this study since the sole source of the data is the corpus data. Qualitative research method is used in order to find the hypotheses from the corpus data which is taken from Sketch Engine. The results demonstrate that the collocations of two node words are dissimilar in the categorization. ‘healthy’ node word indicates that three major semantic preferences are associated with it - human, animal, disease. On the contrary, the semantic preferences of ‘unhealthy’ node word are diverse. Thus, the classification is based on the meaning of the collocations. The collocations with negative meaning occur more frequently than those with positive meaning. It is due to the fact that they use the prefixes –in and –un which create the opposite meaning of the original word. Therefore, the negative semantic prosody is more frequently found the two node words – ‘healthy’ and ‘unhealthy’.